ʺKettle juggling as an effective means of general physical training of studentsʺ. - Derevenets, S.; Litovchenco , V. (Problems of Engineer-Pedagogical Education, 2024)
Abstract. This paper addresses the incorporation of lightweight kettlebell juggling elements in the general physical training (GPT) of students. The primary focus is on juggling as a health-improving method for various student categories. The article provides a detailed description of the specifics of kettlebell juggling training sessions, both in individual and group approaches. It presents the simplest basic exercises that constitute an athlete's performance, along with criteria for evaluating performance. The authors explore the potential of organizing regular kettlebell all-around competitions for health purposes, encompassing classical kettlebell exercises. Additionally, the authors highlight the rehabilitative effects of kettlebell juggling, emphasizing its health benefits.Kettlebell juggling is particularly beneficial for health, especially for individuals with a low level of physical fitness, as it avoids overloading the body. Training exertion includes the following effects: • mobilize and adjust the spine; • develop the ability to balance; • develop respiratory functions; • affect the athlete's nervous system; • develop correct posture. In the scientific work, the authors also pay attention to safety technology. The safety technique in kettlebell juggling is specific, it differs slightly from other strength sports. If we take, for example, such strength sports as weightlifting, powerlifting, as well as the classic push or push of weights in a long cycle, then the increase in the result depends on the weight of the projectile, the number and speed of lifts at a particular time. In a weightlifter, when lifting a projectile, the load on the spine and joints is very high, and if you do not pay due attention to safety techniques when performing exercises, as well as do not perform preventive exercises (hyperextension, "pumping" of the knee joints, etc.), you can get injured. As for kettlebell juggling, the load on the athlete's skeleton is constant, the weight of the projectile is small, the exercises are performed in a swinging, gentle mode, so the load on the spine and joints is more or less mild. But the juggler performs exercises with a large amplitude, throws are performed up to 5-6 meters up, so you need to be very attentive and careful, the performance technique must be brought to perfection, you do not need to perform juggling exercises when you are tired and lack of sleep. The authors also pay some attention to adaptation. A juggler is not only an athlete, but also an artist and a circus performer. Juggling is a performance that requires physical, intellectual and psychological stress. The burden of responsibility is very large, publicity, the number of attempts is limited, high requirements for the clarity of the execution of exercises, the need to make quick operational decisions, and to achieve a good result in the competition, you need to be confident not only in yourself but also in your partners (if the competition is team). In the process of adaptation, mental stability is formed in athletes, which ensures its manifestation in a difficult environment during competitions, in a state of stress, etc. Illustrations of a set of kettlebell exercises used in kettlebell juggling are provided (table №1).